2005
DOI: 10.1002/humu.9311
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic manifestation is associated withALK1 in hereditary hemorrhagic telangiectasia: Identification of five novelALK1 and one novelENG mutations

Abstract: Hereditary hemorrhagic telangiectasia (HHT), or Osler-Rendu-Weber syndrome, is a heterogeneous inherited disorder characterized by multi-systemic vascular dysplasia and wide variation in its phenotypic expression. Hepatic manifestation is seen in about 8 to 30 % of the patients. The molecular basis for liver involvement is unknown. We screened the two known HHT disease loci, the ALK1 (ACVRL1) and ENG genes, for mutations in a clinically well-characterized group of HHT patients with or without liver involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
3
24
0
2
Order By: Relevance
“…Among the Italian patients, we found a high prevalence of ALK1-mutation-carrier probands (41) compared to that for the ENG-mutation-carrier probands (20). Such results, in agreement with the French (Lesca et al, 2004) and Spanish data (Fernandez-Lopez et al, unpublished data reported in the 6 th HHT Scientific Conference, Lyon, 21-23 April 2005), are in contrast with studies on other populations (Letteboer et al, 2005;Abdalla et al, 2005;Kuehl et al, 2005;Schulte et al, 2005). In the French population described by Lesca et al (2004), the higher prevalence of ALK1 mutations was due to both the founder effect and presence of mutational hot-spots which occurred in ALK1 but not in ENG since the authors observed 36 and 34 different mutations in ALK1 and ENG, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Among the Italian patients, we found a high prevalence of ALK1-mutation-carrier probands (41) compared to that for the ENG-mutation-carrier probands (20). Such results, in agreement with the French (Lesca et al, 2004) and Spanish data (Fernandez-Lopez et al, unpublished data reported in the 6 th HHT Scientific Conference, Lyon, 21-23 April 2005), are in contrast with studies on other populations (Letteboer et al, 2005;Abdalla et al, 2005;Kuehl et al, 2005;Schulte et al, 2005). In the French population described by Lesca et al (2004), the higher prevalence of ALK1 mutations was due to both the founder effect and presence of mutational hot-spots which occurred in ALK1 but not in ENG since the authors observed 36 and 34 different mutations in ALK1 and ENG, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The link between ACVRL1 mutations and a higher prevalence of liver arteriovenous shunts has been suggested from previous, although not all, studies. [21][22][23] We confirm here a close link between ACVRL1 mutations and hepatic involvement but also demonstrate for the first time that the proportion of patients with ACVRL1 mutations increases as the severity of the liver disease increases. Moreover, in our experience, almost all patients investigated for severe liver involvement or referred for liver transplantation carry ACVRL1 mutations (not shown).…”
Section: Discussionsupporting
confidence: 80%
“…We then compared our results to the screenings recently published by other groups on different European populations [Germany (Kuehl et al 2005;Schulte et al 2005;Wehner et al 2006), Spain (Fernandez-L et al 2006), Denmark (Brusgaard et al 2004), France (Lesca et al 2004, Netherlands (Letteboer et al 2005)] and to the work of Lenato et al 2006 on a smaller group of Italian patients (see Figs. 1,2).…”
Section: Resultsmentioning
confidence: 99%